2008
DOI: 10.1037/1099-9809.14.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the effects of spiritual well-being on long-term psychological and behavioral outcomes within a sample of homeless women.

Abstract: The present study examines ethnicity as a moderator variable between spiritual well-being (SWB) and psychological and behavioral outcomes. Participants included in this analysis were 88 African American (46.6%) and 101 non-African American (total N = 189) homeless mothers. Through structured interviews conducted at 3-month intervals over a period of 15 months, data were collected on spiritual well-being, mental health, trauma symptoms, substance use, parenting, and child behavior. Hierarchical linear model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The differential findings related to religious versus existential well-being raise questions about how spirituality is experienced. In a study of ethnic differences on the effects of spiritual well-being, researchers suggested that the connection between spiritual and psychological well-being is unique for African American women who live at the intersection of race, class, and gender (Douglas, Jiminez, Lin, & Frisman, 2008). Similarly, study findings likely reflect a collective and community oriented cultural value in which women strive to find meaning in ways that are personally valuable and possibly more broadly defined than religiously prescribed (Sales, Merrill, & Fivush, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The differential findings related to religious versus existential well-being raise questions about how spirituality is experienced. In a study of ethnic differences on the effects of spiritual well-being, researchers suggested that the connection between spiritual and psychological well-being is unique for African American women who live at the intersection of race, class, and gender (Douglas, Jiminez, Lin, & Frisman, 2008). Similarly, study findings likely reflect a collective and community oriented cultural value in which women strive to find meaning in ways that are personally valuable and possibly more broadly defined than religiously prescribed (Sales, Merrill, & Fivush, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The SWBS has good test-retest reliability across four studies (0.86-0.99) (Bufford, Paloutzian, & Ellison, 1991) and is positively associated with self-concept and emotional adjustment and negatively correlated with poor health and a lack of purpose in life. The SWBS has been used extensively with non-white samples, including African-Americans (Douglas, Jimenez, Lin, & Frisman, 2008). Coefficient alpha for the current sample was 0.90 for the total scale, 0.89 for the religious well-being subscale, and 0.82 for the existential well-being subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Spiritual well-being encompasses existential (purpose and meaning in life) and religious (relationship with God) aspects (Paloutzian & Ellison, 1982). Among African Americans, existential and religious well-being combined and independently have been linked to adjustment (Douglas, Jiminez, Lin, & Frisman, 2008; Kaslow et al, 2002; Mitchell et al, 2006; Watlington & Murphy, 2006). Existential well-being has been associated with better quality of life (Dalmida, Holstad, Dilorio, & Laderman, 2011).…”
Section: Spiritual Well-being: Culturally Relevant Protective Factormentioning
confidence: 99%